Islamic Smart City: Study of Literacy and Inclusion in Financial Behavior and Empowerment of Micro, Small and Medium Enterprises (MSMEs) - Raja Sakti Putra Harahap; Asmuni Asmuni; Andri Soemitra (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This article aims to examine; 1. The effect of financial literacy on the financial behavior of MSME entrepreneurs in Binjai City. 2. The effect of financial inclusion on the financial behavior of MSME entrepreneurs in Binjai City. 3. The influence of Islamic Smart City on the financial behavior of MSME entrepreneurs in Binjai City. This study used a quantitative method with a research instrument in the form of a questionnaire. The research sample was 154 MSME actors in Binjai City. While the data analysis technique uses PLS-Structural Equation Modeling (SEM) analysis based on variance or Partial Least Square (PLS). The results of the study show that: 1. Financial literacy which consists of indicators of general financial knowledge, savings and loans, insurance, and investment has no significant effect on the financial behavior of MSME entrepreneurs in Binjai City. 2. Financial inclusion consisting of indicators of the dimensions of access, dimensions of use, dimensions of quality, and dimensions of welfare has a significant effect on the financial behavior of MSME entrepreneurs in Binjai City. 3. Islamic Smart City which consists of Smart Economy, Smart Mobility, Smart Environment, Smart People, Smart Living and Smart Governance indicators has a significant effect on the financial behavior of MSME entrepreneurs in Binjai City. 4. Financial literacy and inclusion as well as Islamic Smart City have a significant effect on the financial behavior of MSME entrepreneurs in Binjai City.